Governance by conference? Actors and agendas in Arctic politics - Steinveg, Beate (UiT Norges arktiske universitet, 2021)
The Arctic has become a core national priority for the Arctic states, and the region has attracted the interest of non-Arctic state actors. Since the 1990s, the Arctic has been characterized by cooperative institutions forming a complex picture of transnational collaboration. Increased interest towards the region, catalyzed by geopolitical changes and the impacts of climate change, has also been accompanied by a growth in the establishment of conferences on Arctic issues. Yet, there has been no systematic examination of the role and functions of conferences in Arctic governance. This thesis contributes to filling this knowledge gap, by examining conferences as a new element of the soft-law dimension of the Arctic governance architecture – operating in the intersection between sovereign states and formalized cooperative arrangements. Through an in-depth case study of the two largest arenas for international dialogue in the region: the Arctic Frontiers (Tromsø) and the Arctic Circle Assembly (Reykjavik), and three mechanisms – actors, agenda setting, and the Arctic governance architecture – as points of influence, the thesis concludes on the functions of conferences within Arctic governance. I argue for interaction through conferences as a solution to the challenges of managing the growing number of agenda issues and governance arrangements, and to balance the interests and activities of new stakeholders with those of Arctic rights-holders. Firstly, I demonstrate how Arctic issues have developed a global dimension, and that the dynamic and multidimensional platform provided by conferences has contributed to a broader and refocused globalized agenda. While not governing arenas, I establish how conferences blur the line between governance and dialogue. Secondly, the shift in the Arctic agenda has led to changes in who proclaim to be legitimate stakeholders. The involvement of non-Arctic states can prove central for diplomatic relations, and balanced social and economic development of the Arctic. From this, I argue ...